Degradable Slow-Release Fertilizer Composite Prepared by Ex Situ Mixing of Inverse Vulcanized Copolymer with Urea - Manzoor Ghumman, A.S. (MDPI, 2022)
To improve the crop yield and nitrogen uptake efficacy, a novel slow-release urea composite fertilizer (SUCF) was developed using inverse vulcanized copolymer with better biodegradation and nutrient release longevity. Copolymers were synthesized via inverse vulcanization of jatropha oil, and their properties were evaluated using thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), powdered-X-ray diffractometry (p-XRD), and scanning electron microscopy (SEM). SUCFs were developed by ex situ mixing of inverse vulcanized copolymer with urea powder using mechanical mixer, and their properties were evaluated using Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). FTIR spectra of developed fertilizer possesses the urea characteristics peaks along with the undisturbed peaks representing copolymer, confirming the mechanical mixing and that no reaction took place. SEM images of the SUCFs compared with images of copolymer revealed the appearance of new isolated particles with different morphology; EDX mapping showed that these particles represent the urea added to the copolymer. Nitrogen release longevity of developed fertilizers was evaluated in both soil and distilled water. The leaching test revealed that only 70 of the total nitrogen of SUCF prepared from 50 wt sulfur copolymer was released after 16 days of incubation in distilled water, whereas it released only 35 nitrogen after 20 days in soil. The biodegradability of all copolymers developed was investigated by burying in soil and it revealed their biodegradable nature as weight loss was observed, which increased with the increase of incubation period. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.